Comparison of clinical characteristics and outcomes among different age groups in elderly patients with hip fracture surgery - Qingwen Cao; Lize Zhang; Xingzhi Cai; Wenlong Shen; Haoran Wu; Ailan Yu; Xia Xu (PLoS ONE, 2025)
Background Studies comparing the clinical characteristics and outcomes among different age groups in elderly patients with hip fractures are scarce. Thus, this study aimed to 1) analyze the clinical characteristics and postoperative outcomes among different age groups in elderly patients undergoing fracture surgery. 2) provide more evidence-based basis for perioperative management. Methods In the retrospective study, 909 patients aged 65 years and above who underwent hip fracture surgery at Liaocheng People’s Hospital between October 2020 and April 2023 were categorized into three groups based on age: young old group (YO group, 65–74 years old), middle old group (MO group, 75–84 years old), and oldest-old group (OO group, ≥ 85 years old). Then, their pre-fracture conditions, fracture causes and type, anesthesia and surgical details, postoperative complication and outcomes were compared. Results In the YO, MO, and OO groups, the male-to-female ratios were 1:2.1, 1:1.8, and 1:2.3, respectively (P = 0.293). The proportion of patients with American Society of Anesthesiologists (ASA) ≥ III, Nottingham hip fracture score (NHFS) ≥ 5 and preoperative activity tolerance < 4 metabolic equivalents (METs) increased sequentially (P < 0.001), across the YO, MO, and OO groups, whereas the proportion of those with three or more internal medicine comorbidities sequentially decreased (P < 0.001). All three groups were primarily injured by falls and the older the age, the higher the proportion of injuries caused by falls (P = 0.006). There was a higher proportion of femoral neck fractures in the YO group and a higher incidence of intertrochanteric fracture in the OO group (P < 0.001). The proportion of patients undergoing spinal anesthesia in the HO group (78.8%) was higher than that in the MO (59.9%) and YO groups (55.1%) (P < 0.001). Additionally, the proportion of postoperative intensive care unit (ICU) admissions (10%) was higher in the OO group compared to the MO (6.2%) and YO groups (4.5%) (P = 0.032). Meanwhile, the incidence of postoperative complications progressively increased in the YO, MO, and OO groups (P < 0.001). The mortality rates of the HO group at the hospital, 30 days postoperatively, and 90 days postoperatively were 6.3%, 9.6%, and 13.3%, respectively, which were significantly higher than those of the MO (2.7%, 3.6%, 6.2%) and the YO groups (1.2%, 1.8%, 2.4%) (P < 0.001). Conclusions The majority of elderly patients undergoing hip fracture surgery were female, with falls being the predominant cause of injury. Increasing age was correlated with poorer preoperative mobility, a lower prevalence of three or more comorbidities, and a higher likelihood of receiving spinal anesthesia. Lastly, the probability of ICU admission, complications, and mortality rate increased after surgery.